Tendências de publicações brasileiras sobre alfabetização científica no ensino de Biologia (1997 - 2021) - Andrade, Maria José Dias de (2022)
Conceived from Freire’s concept of literacy, the Scientific Literacy (SL) is incorporated into the educational context from its conception as a political act that aims at the emancipation and citizenship formation of students, providing them with the necessary skills to exercise their right to social practice, from the mobilization of scientific knowledge. In this sense, the present study aimed as objective investigate the trends of Brazilian research on SL on Biology Teaching, published on the two main scientific events in this area, the Encontro Nacional de Pesquisa em Educação em Ciências (ENPEC) and the Encontro Nacional de Ensino em Biologia (ENEBIO), and the Catálogo de Teses e Dissertações da CAPES, covering the period between 1997 and 2021. It is assumed that the memories printed in the annals of the two main events of Science and Biology Teaching in the country, and in the Catálogo de Teses e Dissertações da CAPES, will provide the knowledge about how research on SL has evolved over spaces and time in the Brazilian scenario, evidencing the paths taken and the clues about the trajectories to follow. It was used as theoretic-methodological assumptions the quantitative approach and the method of state of knowledge, under the focus of content analysis of categorical type. It was based on pre-established categories to analyze the data covering the period between 1997, when the I ENPEC was held, and 2021, year of the most recent edition of this meeting and of the ENEBIO. The results found indicate the significative growth of the general number of papers on SL published in the investigated locus, with research on Biology Teaching showing a stagnation in the last few years. There is a predominance of research coming from the South-Southeast axis, with the Northeast region emerging as an element of mitigation of these regional asymmetries. Most of the works did not receive financial incentive, nor were they articulated to other projects, as well as, the authorship and orientations are, in its great majority, punctual. Most of the investigations were developed in High School and Higher Education, dealing with various themes of Biology Teaching, operationalized mainly from the Content-Method relationship, through descriptive and interventive research, with the growth of the latter category in recent years, thus evidencing the pragmatic character of much of the analyzed work. It was observed the maintenance of gaps identified in general research on Biology Teaching, such as the erasing of research developed in EJA, Special Education and Non-Formal Education, as well as the silencing of the subthemes Anatomy, Embryology and Biochemistry, and the thematic focuses School Organization and History and Philosophy of Science. From the analyzed categories it was possible to observe elements that characterize the historical evolution and the movements made by researchers who work with SL in Biology Teaching, revealing continuities and changes related to general research in Science Education, as well as the permanence of thematic and methodological trends in relation to general works on Biology Teaching.